ANALYSIS OF DOMINANT FACTORS INFLUENCING THE COMPANY’S LIQUIDITY DECLINE - Ditarosa Taurista; Mustika Putri Fatimah; Agus Sukoco; Elok Damayanti; Liem Gai Sin (Journal of International Conference Proceedings (JICP), 2018)
The purpose The objective of the research is to find the variable that gives significant influence to the liquidity of the port company, which is seen from the amount of cash / bank, accounts receivable, inventory and debt with the study conducted at Surabaya Port Company Indonesia. Method, The research data uses financial statements published by the company for the period of 2010 to 2014. This study examines the influence of four independent variables (the amount of cash / bank, accounts receivable, inventory and debt) to one variable bound liquidity.Analysis technic to test the hypothesis using linear regression multiple with SPSS version 20. Result, The results showed that the most dominant factor influenced the decrease of corporate liquidity (case study PT.Pelabuhan Indonesia Surabaya Branch) is the factor of cash / bank. The findings The findings of this study is the value of the liquidity of a port firm is largely determined by the availability of the money in the cash and bank owned by the company. This leads the company to always keep the amount of funds deposited in cash and bank enough to maintain the company's liquidity. Keywords: Ratio, liquidity, decline, port firm